The effect of transfer pricing and tax leverage on tax avoidance in the energy sector - Amanda Elisabech Simanjuntak; Suparna Wijaya (Educoretax, 2026)
This study examines and analyzes the effect of transfer pricing and tax leverage on tax avoidance in energy sector companies, with profitability as a control variable. Tax avoidance is measured using the Book-Tax Difference (BTD) proxy, transfer pricing through related-party transactions, and leverage in accordance with the debt-to-equity ratio limitation of 4:1 stipulated under Minister of Finance Regulation No. 169/PMK.010/2015. This research is motivated by Indonesia's suboptimal tax-to-GDP ratio and the persistent inconsistency of prior empirical findings on the determinants of tax avoidance. Employing a quantitative approach, the study focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Samples were selected using purposive sampling, yielding 57 companies with 285 observations. Hypothesis testing was performed using panel data regression with the Random Effects Model, estimated through Generalized Least Squares (GLS) in STATA version 17. The results reveal that transfer pricing has a positive and significant effect on tax avoidance, indicating that intra-group related-party transactions remain an instrument of corporate tax planning through profit shifting to lower-tax jurisdictions. Conversely, tax leverage has no significant effect on tax avoidance, suggesting that the regulatory debt-to-equity limitation effectively restrains the use of excessive debt as a tax avoidance strategy, with debt financing directed primarily toward operational and investment needs. These findings reinforce agency theory and underscore the importance of strengthening transfer pricing regulation and supervision to safeguard state tax revenue potential.